COMPUTATIONAL GEOMETRY: THE CONVEXHULL PROBLEM - Ruiz Lizama, Edgar (2005)
The objective of this work is to show fundamental concepts of computational geometry and one solution for the convex hull problem, using the Graham algorithm. The authors use the Java language programming in order to implement the solution.